2020
DOI: 10.1002/ente.202000756
|View full text |Cite
|
Sign up to set email alerts
|

The Thermodynamics‐Based Benchmarking Analysis on Energy‐Efficiency Performance of CO2 Capture Technology: Temperature Swing Adsorption as Case Study

Abstract: Climate issues, especially linked to the greenhouse effect and global warming, are receiving increasing attention. The most direct cause is the overproduction of anthropogenic carbon dioxide. Carbon capture and storage (CCS) is one of the main strategies for mitigating and controlling CO 2 emissions from large emission sources, as well as achieving large-scale CO 2 emission reductions. [1] In October 2018, the Intergovernmental Panel on Climate Change (IPCC) released the 1.5 C Special Report in Incheon, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 85 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…Peh et al 47 reported a single-stage variational temperature adsorption (TSA) process in which a simulation-based approach compared the equilibrium and kinetics of a CO 2 /N 2 /H 2 O ternary system with four-and five-step cycles. Chen et al 48 used performance data from previous studies to conduct a baseline analysis of TSA cases. An analytical framework for energy efficiency evaluation in 49 established a numerical model for the design and performance analysis of carbon dioxide capture.…”
Section: Introductionmentioning
confidence: 99%
“…Peh et al 47 reported a single-stage variational temperature adsorption (TSA) process in which a simulation-based approach compared the equilibrium and kinetics of a CO 2 /N 2 /H 2 O ternary system with four-and five-step cycles. Chen et al 48 used performance data from previous studies to conduct a baseline analysis of TSA cases. An analytical framework for energy efficiency evaluation in 49 established a numerical model for the design and performance analysis of carbon dioxide capture.…”
Section: Introductionmentioning
confidence: 99%